Two new species of Aloe (Asphodelaceae) from the Eastern Humid Forest of Madagascar - Rakotoarisoa, Solofo E.; Rakotonasolo, Franck; Rabarijaona, Romer N.; Grace, Olwen M. (Phytotaxa, 2020)
Two new species of Aloe were found in the eastern rainforest of Madagascar during a Kew Madagascar Conservation Centre (KMCC) Team expedition in November 2014. The first species, Aloe vatovavensis is rare in this habitat. The second, Aloe rakotonasoloi, exhibits characters that are intermediate between the features of Aloe s.str. and the related genus Lomatophyllum (now Aloe sect. Lomatophyllum). Despite being one of the most species-rich areas for plant diversity, only a few species of Aloe—typically those of Aloe sect. Lomatophyllum—have been recorded in the eastern rainforest of Madagascar to-date.